2021
DOI: 10.1111/ajt.16369
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in transplant recipients: The Spanish experience

Abstract: We report the nationwide experience with solid organ transplant (SOT) and hematopoietic stem cell transplant (HSCT) recipients diagnosed with coronavirus disease 2019 in Spain until 13 July 2020. We compiled information for 778 (423 kidney, 113 HSCT, 110 liver, 69 heart, 54 lung, 8 pancreas, 1 multivisceral) recipients.Median age at diagnosis was 61 years (interquartile range [IQR]: 52-70), and 66% were male. The incidence of COVID-19 in SOT recipients was two-fold higher compared to the Spanish general popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
230
4
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(259 citation statements)
references
References 52 publications
14
230
4
11
Order By: Relevance
“…The median hospital LOS of 10 days (IQR 5-19) is slightly shorter to that reported in a large multicenter Spanish study (LOS of 12 days [IQR 7-21]). 4 Another study of 98 SOTR hospitalized for COVID-19 with 28-day follow-up reported a median ICU LOS of 11 days, similar to our findings, and described a shorter median ventilation duration (9 vs 12 days in our study), but only examined the first 14 days after hospitalization. 2 The longer duration of MV reported here highlights the importance of adequate follow-up time on measures of resource utilization since estimates from the longest hospital courses would not be captured at shorter intervals.…”
Section: Healthcare Resource Use Among Solid Organ Transplant Recipiesupporting
confidence: 89%
See 2 more Smart Citations
“…The median hospital LOS of 10 days (IQR 5-19) is slightly shorter to that reported in a large multicenter Spanish study (LOS of 12 days [IQR 7-21]). 4 Another study of 98 SOTR hospitalized for COVID-19 with 28-day follow-up reported a median ICU LOS of 11 days, similar to our findings, and described a shorter median ventilation duration (9 vs 12 days in our study), but only examined the first 14 days after hospitalization. 2 The longer duration of MV reported here highlights the importance of adequate follow-up time on measures of resource utilization since estimates from the longest hospital courses would not be captured at shorter intervals.…”
Section: Healthcare Resource Use Among Solid Organ Transplant Recipiesupporting
confidence: 89%
“…Several studies have described these measures but are limited by small sample size, short or variable durations of follow-up, or single-center experiences. [2][3][4] A recent multicenter study by Coll et al reports on hospital LOS in SOTR with COVID-19, but follow-up time was not standardized and neither MV duration nor ICU LOS was measured. 4 To address these limitations, we performed analyses from data in a prospective, multicenter registry of 376 SOTR hospitalized with COVID-19 with standardized 28-day follow-up, which has been previously described.…”
Section: Healthcare Resource Use Among Solid Organ Transplant Recipiementioning
confidence: 99%
See 1 more Smart Citation
“…However, reporting bias certainly occurred, especially in large cohorts with voluntary reporting of cases and limited testing availability early in the pandemic for non‐hospitalized patients. In recent international cohorts, 78–89% of identified patients were hospitalized which is higher than in the general public, although this also may reflect reporting or testing bias of differential health care utilization for transplant patients 17,90 . Once hospitalized, rates of transition to the intensive care unit ranged from 8.6% in the Netherlands to 18%–34% in other cohorts internationally 15,17,33,79,84,91,92 .…”
Section: Epidemiology and Outcomesmentioning
confidence: 99%
“…A European study conducted by the ERA-EDTA from the French and Spanish registry yielded an average infection rate of 14/1000 transplants at risk [ 7 ]. The Spanish registry [ 8 ], with a longer period of observation, showed an incidence of 17.7/1000 transplants, while the French registry [ 9 ], with a shorter observation period, showed an incidence of 9.5/1000 transplants. The kidney registry of the Dutch-speaking Belgian Society of Nephrology reports a similar incidence of 14.0/1000 transplants [ 10 ].…”
Section: Epidemiology Of Covid-19 In Renal Transplant Patients Acrossmentioning
confidence: 99%